Dysferlin links excitation–contraction coupling to structure and maintenance of the cardiac transverse–axial tubule system. Issue 7 (23rd June 2020) - Hofhuis, Julia; Bersch, Kristina; Wagner, Stefan; Molina, Cristina; Fakuade, Funsho E; Iyer, Lavanya M; Streckfuss-Bömeke, Katrin; Toischer, Karl; Zelarayán, Laura C; Voigt, Niels; Nikolaev, Viacheslav O; Maier, Lars S; et al.
Abstract: Aims: The multi-C2 domain protein dysferlin localizes to the T-Tubule system of skeletal and heart muscles. In skeletal muscle, dysferlin is known to play a role in membrane repair and in T-tubule biogenesis and maintenance. Dysferlin deficiency manifests as muscular dystrophy of proximal and distal muscles. Cardiomyopathies have been also reported, and some dysferlinopathy mouse models develop cardiac dysfunction under stress. Generally, the role and functional relevance of dysferlin in the heart is not clear. The aim of this study was to analyse the effect of dysferlin deficiency on the transverse–axial tubule system (TATS) structure and on Ca 2+ homeostasis in the heart. Methods and results: We studied dysferlin localization in rat and mouse cardiomyocytes by immunofluorescence microscopy. In dysferlin-deficient ventricular mouse cardiomyocytes, we analysed the TATS by live staining and assessed Ca 2+ handling by patch-clamp experiments and measurement of Ca 2+ transients and Ca 2+ sparks. We found increasing co-localization of dysferlin with the L-type Ca 2+ -channel during TATS development and show that dysferlin deficiency leads to pathological loss of transversal and increase in longitudinal elements (axialization). We detected reduced L-type Ca 2+ -current ( I Ca, L ) in cardiomyocytes from dysferlin-deficient mice and increased frequency of spontaneous sarcoplasmic reticulum Ca 2+ release events resulting in pro-arrhythmic contractions. Moreover, cardiomyocytes from dysferlin-deficient mice showed an impaired response to β-adrenergic receptor stimulation. Conclusions: Dysferlin is required for TATS biogenesis and maintenance in the heart by controlling the ratio of transversal and axial membrane elements. Absence of dysferlin leads to defects in Ca 2+ homeostasis which may contribute to contractile heart dysfunction in dysferlinopathy patients.